2011
DOI: 10.1007/s10765-011-1041-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Hysteresis in Thin-Film Platinum Resistance Thermometers

Abstract: Thin-film platinum resistance thermometers (PRTs) are generally manufactured using the deposition of a thin platinum film on an alumina substrate and a laser-trimming method. Because of the strong adhesion between the platinum thin film and the alumina substrate, the PRTs inevitably have strain over the operating temperature range. This causes anomalies and instabilities in the resistance versus temperature characteristics (R-T ). The most prominent and observable effect of thermally induced strain is the ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…The value obtained from the experimental data was in strong agreement as well. The second order polynomial (4) was employed in the correct format which in turn returned the characteristic equation specified for the manufacture (5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value obtained from the experimental data was in strong agreement as well. The second order polynomial (4) was employed in the correct format which in turn returned the characteristic equation specified for the manufacture (5).…”
Section: Resultsmentioning
confidence: 99%
“…Many papers reported on the design and development of platinum thin film RTDs and among them few researchers have analyzed the thermal hysteresis effects [5][6][7][8], thermal strain effects [9], thin film thickness effects [2], stagnation temperature [10], degradation effects at high temperature [11] and the long term stability [6,12] of the platinum RTDs. However temperature coefficient of resistance (TCR) plays an important role in determining the sensitivity of the RTD elementas it characterizes the average temperature chance of a 1Ω RTD.…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainties in between ±1 K (1σ) are expected for a class A PT100 as defined by the IEC 60751 at absolute temperatures around 400°C. Gam et al [12] and Zvizdić et al [13] investigate the thermal hysteresis effects in industrial platinum resistance temperature detectors. Both groups observed a hysteresis around 0.1 K for absolute temperatures of 400°C.…”
Section: Pt100 Calibration and Preliminary Studymentioning
confidence: 99%
“…For engine applications, the primary limitation of the thin-film PRT is its temperature capability, which is typically restricted to 500 o C. Consideration should also be given to potential hysteresis in the resistance-temperature characteristic, as well as the possible impact of thermal cycling. For example, Gam et al (2011) have reported the measurement of hysteresis for 30 thin-film PRT sensors when cycled between 0 and 500 o C. A range of hysteresis levels was observed in these devices (between 16 and 156 mK) although after six repeat thermal cycles these reduced to less than 53 mK for all sensor types tested. In the current work a similar hysteresis study has been conducted (over a smaller temperature range) and is presented in the next section.…”
Section: Temperature Sensing Elementsmentioning
confidence: 99%
“…The temperature range considered in this exercise is thus limited to the expected flow temperature range used during the dynamic calibrations. If the sensors were to be used over a wider temperature range (as may be the case in engine test campaigns) this exercise would need to be repeated over an appropriate temperature range (see for example Gam et al, 2011). Additionally, the opportunity was taken to establish whether mechanical vibration leads to a change in static calibration behaviour.…”
Section: Temperature Sensing Elementsmentioning
confidence: 99%